1987
DOI: 10.1007/bf00379264
|View full text |Cite
|
Sign up to set email alerts
|

Pocket gophers (Geomys bursarius), vegetation, and soil nitrogen along a successional sere in east central Minnesota

Abstract: Pocket gophers (Geomys bursarius: Geomyidae Rodentia) are shown to affect soil resources and thus, indirectly, vegetation. Gophers reduce average soil nitrogen near the surface and increase point-to-point heterogeneity of soil nitrogen by moving nitrogen-poor subsurface soil to the soil surface. Data from 22 old fields at Cedar Creek Natural History Area, Minnesota, USA show correlations of soil nitrogen, vegetation, and gopher mounds that are consistent with this indirect mechanism by which gophers affect loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
2
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 16 publications
9
99
2
2
Order By: Relevance
“…Similar shifts in dominance have been observed in other grasslands (Foster and Stubbendieck, 1980;Tilman, 1983;Inouye et al, 1987a;Collins, 1989;Martinsen et al, 1990) and subalpine meadows (Sherrod et al, 2005). Greater survival and more rapid emergence of dicots following burial has been attributed to their strong clonal potential (e.g., Collins, 1989;Umbanhowar, 1995) and abundant storage of carbon in below-ground structures (Webber and May, 1977;Sherrod et al, 2005, see also Lezberg et al, 1999).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Similar shifts in dominance have been observed in other grasslands (Foster and Stubbendieck, 1980;Tilman, 1983;Inouye et al, 1987a;Collins, 1989;Martinsen et al, 1990) and subalpine meadows (Sherrod et al, 2005). Greater survival and more rapid emergence of dicots following burial has been attributed to their strong clonal potential (e.g., Collins, 1989;Umbanhowar, 1995) and abundant storage of carbon in below-ground structures (Webber and May, 1977;Sherrod et al, 2005, see also Lezberg et al, 1999).…”
Section: Discussionsupporting
confidence: 57%
“…Six species were more abundant on mounds, but all of these were also present in meadows. Thus, mounds in this system clearly do not serve as microsites for germination of fugitive or subordinate species as they do in other systems (Laycock, 1958;McDonough, 1974;Platt, 1975;Foster and Stubbendieck, 1980;Inouye et al, 1987a;Collins, 1989;Gibson, 1989;Hartway and Steinberg, 1997). In fact, the rarest taxa -those with one or two occurrences -were restricted to meadow plots.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Jones et al (1997) argued that the effect of ecosystem engineering on species richness at a scale that includes both engineered patches and patches unmodified by that particular ecosystem engineer-the landscape scalewould almost inevitably be positive due to an increase in habitat diversity. Several studies have suggested that ecosystem engineers increase landscape-scale species richness by creating new habitats and allowing species that would otherwise be excluded to persist (Collins and Uno 1983, Inouye et al 1987, Guo 1996, Ceballos et al 1999). For example, Wright et al (2002) estimated that by creating wetlands, beaver increase the number of herbaceous plant species in riparian zones by 33%.…”
Section: Predicting the Effect Of Ecosystem Engineering On Species Rimentioning
confidence: 99%
“…Furthermore they can also change the structure, organic matter and moisture contents of the soil (Mielke, 1977), and they can even reduce the proportion of available soil nitrogen (Inouye et al 1987). …”
Section: Introductionmentioning
confidence: 99%